STUDENTS’ MOTIVATION AND PREFERENCES TOWARD NATIVE AND NON-NATIVE ENGLISH SPEAKING TEACHERS - Reza Anggriyashati Adara (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2018)
There is a notion that teachers are one of important factors which motivate students to learn English. The present study aims to investigate students’ motivation in learning English with Native English Speaking Teachers (NEST) and Non-native English Speaking Teachers (NNEST) and whether the students are more motivated to learn English with NEST or NNEST. Furthermore, this study examines students’ preferences regarding NEST and NNEST. To obtain the findings, mixed method research was conducted. A set of questionnaires were distributed to thirty students in a private junior high school in Bekasi, Indonesia whereas semi-structured interviews were conducted to two students of same school. The findings show that teacher is an influential factor that motivates students to learn English. Although the respondents are more motivated to learn English from NEST, they do not have certain preferences regarding NEST and NNEST as both teachers help the respondents to learn English in different ways. The findings reveal that NEST are considered better in vocabulary teaching while NNEST teach grammar better.